2017
DOI: 10.3389/fpls.2017.00538
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of a Resistance Gene RpsHN that Controls Phytophthora sojae Using Recombinant Inbred Lines and Secondary Populations

Abstract: Phytophthora root rot (PRR), caused by Phytophthora sojae, has negative effects on soybean yield in China and can be controlled by identifying germplasm resources with resistance genes. In this study, the resistance locus RpsHN in the soybean line Meng8206 was mapped using two mapping populations. Initial mapping was realized using two recombinant inbred line (RIL) populations and included 103 F6:8 RILs derived from a cross of Meng8206 × Linhedafenqing, including 2600 bin markers, and 130 F6:8 RILs derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…Soybean is one of the most important crops in the world. There are a large number of soybean accessions in China, among which many PRR-resistant cultivars/ lines were identified in a previous study [10,13,14,[51][52][53][54][55]. In the present study, the Guizao1 cultivar was PRR resistant to P. sojae PNJ4 and PNJ1, thus differing from the other soybean cultivars tested (Table 1).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Soybean is one of the most important crops in the world. There are a large number of soybean accessions in China, among which many PRR-resistant cultivars/ lines were identified in a previous study [10,13,14,[51][52][53][54][55]. In the present study, the Guizao1 cultivar was PRR resistant to P. sojae PNJ4 and PNJ1, thus differing from the other soybean cultivars tested (Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have identified 17 known Rps genes (alleles) and mapped them to chromosome 3 before RpsGZ, including five alleles of Rps1 (Rps1a, 1b, 1c, 1d, 1 k) [23,24,38,57,58], Rps7 [23], Rps9 [29], RpsYu25 [25], an Rps gene in Waseshiroge [26], RpsYD29 [27], an Rps gene in E00003 soybean within the Rps1 k interval [30], RpsHC18 [10], RpsQ [13], RpsHN [14], RpsX [9], RpsWY [31], and RpsUN1 [28]. Nevertheless, the positional relationships of these Rps genes had not been confirmed, and some of the mapping intervals for these Rps genes overlapped.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic resistance is considered the most effective strategy for preventing or reducing the impact of Phytophthora diseases [4,7].Soybean-breeding programs have relied on resistance conferred by single, dominantly inherited Resistance to Phytophthora sojae (Rps)-genes. More than 30 Rps-genes/alleles have been mapped (S1 Table) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The effectiveness of Rps-mediated resistance is limited as these genes only confer immunity towards specific races of P. sojae.…”
mentioning
confidence: 99%